The Influence of Human Development Index, Gini Ratio, Life Expectancy, and Economic Growth on Poverty in Aceh Province 2018-2022 - Dini Triani; Antoni Sitorus (Proceedings of Bengkulu International Conference on Economics, Management, Business, and Accounting, 2023)
The aim of this research is to determine the influence of HDI, Gini Ratio, life expectancy, and economic growth on district and city poverty in Aceh Province in 2018–2022. This research uses quantitative data. 32 districts or cities were the sample for this research. using types of secondary data sourced from BPS. The analysis was carried out using the panel data regression method selected by REM. HDI, Gini Ratio, and AHH, as well as economic growth, have an effect of 73% (R2 = 0.732320) and can explain the elements that contribute to poverty in districts and cities in Aceh Province. HDI has a negative and significant effect with a coefficient of -0.628582 and a probability of 0.0000<0.05. The Gini ratio with a coefficient of 3.025394 and a prob of 0.01720.05<0.05 has a positive and significant effect; AHH has a coefficient of 0.063478 with a prob value of 0.75>0.05, which is not significant; and the economic growth coefficient is 0.053672 with a prob of 0.0001<0.05, which means it has a negative and significant effect on poverty in the districts and cities of Aceh Province.